O valor do inusitado: como colaborações não convencionais entre marcas ativam emoção, descoberta e intenção de compra na geração z? - Costa, Stephanie Pinheiro (2025)
This research examines how unconventional brand collaborations, those that deliberately break with the traditional Brand Fit paradigm, affect consumers’ affective and cognitive responses and their purchase intention. Drawing on the literature on Co-branding and authenticity (Beverland, 2006; Díaz Ruiz & Cruz, 2023), the study integrates constructs of Brand Love (CARROLL, B A.; AHUVIA, A C., 2006), self–brand connection (ESCALAS, J. E.; BETTMAN, J. R., 2003), serendipity (LIANG et al., 2022), and consumer innovativeness (GOLDSMITH, R. E.; HOFACKER, C. F. , 1991). A theoretical model distinguishes two explanatory paths: an affective one, based on emotional and symbolic ties, and a cognitive one, linked to discovery, curiosity, and openness to novelty. A quantitative survey was conducted with 256 members of Generation Z, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that unconventional collaborations simultaneously trigger affective and cognitive responses, reinforcing love and identification with the partnering brands as well as perceptions of innovation and discovery. However, only the cognitive path, mediated by innovativeness and serendipity, translates into purchase intention, evidencing a full mediation effect. Affective bonds strengthen brand relationships but do not drive behavioral outcomes, suggesting that the market performance of unconventional collaborations stems more from creativity and surprise than from identity coherence. The study contributes to the branding literature by demonstrating that authenticity arises from the experience of discovery and novelty, rather than from symbolic consistency. From a managerial perspective, it highlights that successful collaborations depend on brands’ ability to transform the unexpected into authentic and innovative consumer experiences.